The impact of modern technology and artificial light on insomnia: exploring the role of blue light and screen time - Rio Noramein, Efi Batrisyia; Kamal, Faradeeya; Ismail, Nurul Izzati; Izzaddin, Sri Hannah Zafirah; Saparuddin, Tuah Shahputra; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Md Tajudin, Huriyyah Hamiemah; Ahmad H.Osman, Rahmah; Jaffer, Usman (Global Academic Excellence (GAE), 2025)
This paper explores the impact of modern technology and artificial light on insomnia, with a particular focus on the role of blue light and screen time. The physiological and psychological factors of sleep disturbances are examined, which include the disruption of circadian rhythm due to blue light exposure and how screen time affects brain activity. Blue light also disrupts the production of melatonin which causes delayed sleepiness and lowers the quality of sleep. In addition, this paper explores the effect of screen time on sleep architecture including changes to sleep stages and a decrease in deep sleep. Insomnia is also linked to psychological factors such as increased stress and poor sleep hygiene that are associated with excessive screen time. This paper will also offer practical solutions and the application to current issues, which emphasizes the limitation of screen time before bed and various strategies to reduce blue light exposure.